Thermally Variable, Macrotidal Reef Habitats Promote Rapid Recovery From Mass Coral Bleaching - Schoepf, Verena; Jung, Maria U.; McCulloch, Malcolm T.; White, Nicole E.; Stat, Michael; Thomas, Luke (Frontiers in Marine Science, 2020)
Coral reefs are severely threatened by climate change and recurrent mass bleaching events, highlighting the need for a better understanding of the factors driving recovery and resilience both at the community and species level. While temperature variability has been shown to promote coral heat tolerance, it remains poorly understood how whether this also influences coral recovery capacity. Similarly, few studies have investigated how the presence of cryptic species influences bleaching and recovery responses. Using an integrated ecological, physiological and genomicgenetic approach (i.e. reef-wide coral health surveys as well as chlorophyll a concentration and cryptic species diversity of Acropora aspera), we examined the recovery of both coral communities and their dominant species from the 2016 mass bleaching event in the macrotidal Kimberley region, NW Australia. We show that recovery of coral communities inhabiting adjacent but environmentally contrasting reef habitats differed dramatically following unprecedented bleaching in 2016. Both intertidal (thermally extreme) and subtidal (thermally moderate) habitats experienced extensive bleaching (72-81%), but subtidal coral communities had a greater percentage of severely bleached corals than the intertidal community (76% versus 53%). Similarly, subtidal Acropora aspera corals suffered much greater losses of chlorophyll a than intertidal conspecifics (96% versus 46%). The intertidal coral community fully recovered to its pre-bleaching configuration within six months, whereas the adjacent subtidal suffered extensive mortality (68% loss of live coral cover). Despite the presence of three cryptic genetic lineages in the dominant coral species, the physiological response of A. aspera was independent of host cryptic genetic diversity. Furthermore, both intertidal and subtidal A. aspera harbored symbionts in the genus Cladocopium (previously clade C). Our findings therefore highlight the important role of tidally-controlled temperature variability in promoting coral recovery capacity., and While the underlying physiological and molecular mechanisms require further investigation, we propose that shallow reef environments characterized by strong environmental gradients may generally promote coral resilience to extreme climatic events. Thermally variable reef environments may therefore provide important spatial refugia for coral reefs under rapid climate change.